GE_GERICHTE C/13154/2013 vom 12. Dezember 2014 - GE Cour de justice (2014)
ACTION EN MODIFICATION; JUGEMENT DE DIVORCE; RELATIONS PERSONNELLES; OBLIGATION D'ENTRETIEN; ENFANT | CC.134; CC.273; CC.276.2; CC.285.1; CC.286.2; CC.12.1.TitFin